Respuesta del cultivo de linaza (Linum usitatissimum L.), a la aplicación de varios niveles de fertilización bajo tres sistemas de siembra en el cantón Cayambe provincia de Pichincha - Chico Ulcuango, Segundo Medardo (2017)
SUMMARY This research was conducted in the province of Pichincha, Cayambe canton, parish of Juan Montalvo in the Central district. It is located in the following coordinates 0 ° 25'58 '' north latitude and 78 ° 13'34 '' west longitude at an altitude of 2,830 meters. seeds from farmers in the area was used as genetic material, the factors studied were Factor A: planting systems. (For blow, steady stream, broadcast) Factor B: fertilization levels of N-P-K (No application; low (32-64-96), average (63-126-189) and high (82-164-246). Design Randomized Complete (DBCA) was applied blocks with a factorial arrangement (A x B) with 3 replications and 12 treatments total of 36 experimental units. All variables were subjected to analysis of variance ANOVA and to determine the statistical difference between treatment means the Tukey test was used at 5% significance. The work done to fulfill the research were; soil analysis, soil preparation, demarcation of plots, planting, irrigation, fertilization, cultivation, pest and disease control, harvesting The variables were evaluated; efciency of fertilizers effectiveness of treatments, plant height, days to flowering, days to harvest, yield and treatments were economically analyzed. The results were; for Systems (planting) not differences in the variables was obtained, confirming that this crop has a good agronomic development in any planting systems. Treatment (Continuous Jet with Media fertilizer application) reached higher averages in terms of efficiency assessments delos fertilizers, plant height and yield per experimental unit, therefore an agronomic optimum development of the plant. The higher return was for treatment (For Media hit with fertilizer application) with $ 11,125.70 USD / ha, lower profitability and the present treatment (continuous jet without application) with an average of $ 7,725.00 USD / ha